An important social problem: allergic rhinitis - Sayın, İbrahim; Cingi, Cemal; San, Turhan; Ulusoy, Seçkin; Acar, Mustafa (ENT Updates, 2013)
Allergic rhinitis (AR) affects the individual's quality of life, psychological well being, cognitive functions and sleep quality. Patients often experience annoying symptoms, mood disorders, decreased work productivity and even loss of work. In pediatric patients undiagnosed or untreated/undertreated AR may be related with learning difficulties which may have an important impact on community's present and future life. AR medication, health care utilization, loss of productivity and work is also related with a cost which is also important for patients, their families and society's economic status. All these factors rendered the disease a social aspect. This article aimed to present the social problems generally related to allergic rhinitis.